Five‐year outcomes of rapid‐deployment aortic valve replacement with the Edwards Intuity valve. Issue 8 (25th May 2021) - Pelce, E.; Porto, A.; Gariboldi, V.; Ben Lagha, A.; Amanatiou, C.; Collart, F.; Theron, A.
Abstract: Background: This report presents 5‐year outcomes of the rapid‐deployment Edwards Intuity valve in a prospective, single‐center study. Methods: All patients who underwent an aortic valve replacement (AVR) with an Edwards Intuity bioprosthesis at La Timone Hospital, Marseille, France, from July 2012 to June 2015 were assessed over a 5‐year follow‐up period. The primary outcome was overall mortality at 5 years. Secondary outcomes were reoperation, overall mortality and stroke, cardiovascular mortality, composite endpoints defined by the updated Valve Academic Research Consortium‐2 (VARC‐2), periprosthetic regurgitation, prosthesis‐patient mismatch, and the need for new pacemaker implantation. Results: In total, 170 consecutive patients were assessed, of which 67.1% were males. The mean age was 76 years, mean EuroSCORE II was 3.5% and 5‐year overall mortality was 12.4%. At 5 years, reoperation was 2.9%, overall mortality and stroke was 4.1% per patient‐year, and cardiovascular mortality was 4.7%. VARC clinical efficacy and VARC time‐related valve safety were achieved in 46.0% and 59.9% of patients, respectively. At one month VARC device success was 71.2% and VARC early safety was 87.1%. At one year, mild and moderate periprosthetic regurgitation were 2.4% and 0.6%, respectively, and moderate and severe prosthesis‐patient mismatch were 18.8% and 4.8%, respectively. Conduction disturbances needing new PPI occurred in 3.5% patients. Conclusion: The 5‐year outcomes of AVR with the Edwards Intuity valve system demonstrate satisfactory midterm safety and excellent haemodynamic performance. Abstract : ​